Utilizing Telemedicine to Improve the Health of the Young Generation - Hidayat, Andra Dwitama; Jayanti, Krisnita Dwi; Lestarjo, Agustinus Nugroho Pudji; Ghafar, Siti Aisyah Abd; Ramli, Nalisha Mohamed; Yusof, Ainuddin Yushar (Journal of Community Engagement and Empowerment, 2025)
The community service activity themed “Utilizing Telemedicine to Improve the Health of the Young Generation” was conducted at Al-Mahrusiyah Elementary School, Kediri City. This initiative was a collaboration between IIK Bhakta Kediri and Universiti Sains Islam Malaysia (USIM). Its objective was to enhance the health literacy of the young generation by utilizing telemedicine technology as an alternative for modern and efficient healthcare services. The community service activity involved 120 participants, consisting of 4th, 5th, and 6th-grade students. Participants attended sessions that included presentations on telemedicine, simulations of telemedicine application usage, and practical online health consultations. Before the activity began, a pretest was conducted to assess the participants’ initial knowledge of telemedicine. The pretest results showed that only 35% of the participants understood the basic concepts of telemedicine. After completing all the activities, a post-test revealed a significant improvement, with 88% of participants able to understand and explain the benefits and workings of telemedicine. Overall, the activity successfully achieved its goals of raising awareness and understanding among students about the importance of telemedicine as a modern solution for healthcare services. In addition to increasing knowledge, the activity also motivated participants to adopt this technology in their daily lives. It is hoped that through innovative approaches like this, the young generation in Kediri City can grow healthier and better prepared to face health challenges in the digital era.